Uso da facilitação visual na gestão de projetos e times ágeis - Miranda, Leonardo Monteiro de (2020)
Every day all types of visual artefacts are created to understand complex information. From doodles describing a fruit or a product, dashboards to facilitate data visualization, flowcharts of login processes or even coloured post-its on the walls, to plan the activities of a work team. We create all kinds of visual models to organize our understanding of a particular topic. However, in an increasingly dynamic, uncertain and complex world, the engagement and time of the professionals involved become increasingly valuable. How to use them to your advantage to plan actions, communicate ideas, generate interest in work teams? This research aims to demonstrate how the application of methods and techniques of Visual Facilitation can assist in agile project management and team development, bringing contributions throughout the work process, from improving the performance of professionals to increasing quality in project deliveries. Interviews with experts and team members and online questionnaires were used as scientific research methodologies. As a final result, the production of support materials for managers and facilitators is planned, as a visual facilitation guide for application in workshops and dynamics in order to develop the visual skills of the participants